2005
DOI: 10.1074/jbc.m503099200
|View full text |Cite
|
Sign up to set email alerts
|

The Small G-protein Arf6GTP Recruits the AP-2 Adaptor Complex to Membranes

Abstract: The small GTP-binding protein ADP-ribosylation factor 6 (Arf6) is involved in plasma membrane/endosomes trafficking. However, precisely how the activation of Arf6 regulates vesicular transport is still unclear. Here, we show that, in vitro, recombinant Arf6GTP recruits purified clathrin-adaptor complex AP-2 (but not AP-1) onto phospholipid liposomes in the absence of phosphoinositides. We also show that phosphoinositides and Arf6 tightly cooperate to translocate AP-2 to the membrane. In vivo, Arf6GTP (but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 36 publications
7
86
0
3
Order By: Relevance
“…AP-2 could function in this context to promote vesicle formation by recruiting proteins that induce membrane curvature, such as epsin (Chen et al, 1998;Ford et al, 2002), or BAR-domain-containing proteins, such as amphiphysin (David et al, 1996;Farsad et al, 2001;Peter et al, 2004;Slepnev et al, 2000). Consistent with this notion, previous studies have shown that Arf6 can bind to AP-2, and cooperate with phosphoinositides to promote AP-2 recruitment to liposomes (Paleotti et al, 2005). Alternatively, the reduced rate of MHCI internalization in AP-2-depleted cells could be indirect.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…AP-2 could function in this context to promote vesicle formation by recruiting proteins that induce membrane curvature, such as epsin (Chen et al, 1998;Ford et al, 2002), or BAR-domain-containing proteins, such as amphiphysin (David et al, 1996;Farsad et al, 2001;Peter et al, 2004;Slepnev et al, 2000). Consistent with this notion, previous studies have shown that Arf6 can bind to AP-2, and cooperate with phosphoinositides to promote AP-2 recruitment to liposomes (Paleotti et al, 2005). Alternatively, the reduced rate of MHCI internalization in AP-2-depleted cells could be indirect.…”
Section: Discussionsupporting
confidence: 62%
“…Recent work showed that Arf6 directly associates with AP-2 in a GTP-dependent manner, and that Arf6 functions cooperatively with PtdIns(4,5)P 2 to recruit AP-2 to membranes (Paleotti et al, 2005). This led the authors to conclude that the function of Arf6 in the context of clathrindependent endocytosis is to promote recruitment of AP-2 to the plasma membrane.…”
Section: Introductionmentioning
confidence: 88%
“…Arf6GTP may participate in clathrin coat assembly, by directly interacting with AP-2 and clathrin (Paleotti et al, 2005;Poupart et al, 2007) and by increasing the PI(4,5)P 2 level at the plasma membrane (Krauss et al, 2003). Consistently, depletion of Arf6 by siRNA affected the endocytosis of the b2AR.…”
Section: Discussionsupporting
confidence: 52%
“…Arf6 functions in both clathrin-dependent and -independent pathways of endocytosis of different membrane cargos such as transferrin receptor, polymeric immunoglobulin receptor, E-cadherin and MHC class I (Altschuler et al, 1999;D'Souza-Schorey et al, 1995;Klein et al, 2006;Palacios et al, 2002;Radhakrishna and Donaldson, 1997). By stimulating the PIP 2 synthesis (Krauss et al, 2003) and by directly interacting with AP-2 and clathrin (Paleotti et al, 2005;Poupart et al, 2007), Arf6 could induce the membrane recruitment of the coated-pit components. The effect of Arf6 on clathrin-mediated endocytosis was also proposed to be regulated by the Arf6-GAP SMAP1, which interacts directly with the clathrin light chain (Tanabe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to ectopically expressed Arf6 in HeLa cells, endogenous Arf6 seems to mark the clathrin-dependent endocytic pathway in CHO cells (D'Souza-Schorey et al, 1995). Recently, studies have shown that Arf6 also plays a major role in clathrin-mediated endocytosis by directly controlling the assembly of the AP-2/clathrin coat (Paleotti et al, 2005;Tanabe et al, 2005). Arf6 has also been shown to be involved in recycling of endocytic membranes via the exocyst effector complex (Prigent et al, 2003).…”
Section: Arf6 Is Not a Specific Marker For Geecs In Cho Cellsmentioning
confidence: 99%